Introduction - Milena Lenderová (Theatrum Historiae)
The International Society for Eighteenth-century Studies (ISECS/SIEDS), the body embracing 27 national societies from around the world, organises an international seminar for young researchers every summer. The organisation of the seminar is entrusted to one of these national societies, which then chooses the topic. In July 2007 the young researchers met in the French city of Montpellier (topic entitled Le corps et ses images: santé, humeurs, maladies / The body and its images: health, humours, illnesses); in September 2009 they met in the Portuguese capital of Lisbon (the topic was Europe and the Colonial World / L’Europe et le monde colonial), and in 2008 they were invited to the seminar by the Czech branch of the ISECS, Česká společnost pro výzkum 18. století (The Czech Society for 18th- century Research). The College of Arts and Philosophy of the University of Pardubice, particularly its Historical Sciences Department, helped to organise the seminar.